Red Flags, Prognostic Impact, and Management of Patients With Cardiac Amyloidosis and Aortic Valve Stenosis: A Systematic Review and Meta-Analysis - Myasoedova, Veronika A.; Conte, Maddalena; Valerio, Vincenza; Moschetta, Donato; Massaiu, Ilaria; Petraglia, Laura; Leosco, Dario; Poggio, Paolo; Parisi, Valentina (Frontiers in Medicine, 2022)
Background Cardiac amyloidosis (CA) has been recently recognized as a condition frequently associated with aortic stenosis (AS). The aim of this study was to evaluate: the main characteristics of patients with AS with and without CA, the impact of CA on patients with AS mortality, and the effect of different treatment strategies on outcomes of patients with AS with concomitant CA. Materials and Methods A detailed search related to CA in patients with AS and outcomes was conducted according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Seventeen studies enrolling 1,988 subjects (1,658 AS alone and 330 AS with CA) were included in the qualitative and quantitative analysis of main patients with AS characteristics with and without CA, difference in mortality, and treatment strategy. Results The prevalence of CA resulted in a mean of 15.4% and it was even higher in patients with AS over 80 years old (18.2%). Patients with the dual diagnosis were more often males, had lower body mass index (BMI), were more prone to have low flow, low gradient with reduced left ventricular ejection fraction AS phenotype, had higher E/A and E/e', and greater interventricular septum hypertrophy. Lower Sokolow–Lyon index, higher QRS duration, higher prevalence of right bundle branch block, higher levels of N-terminal pro-brain natriuretic peptide, and high-sensitivity troponin T were significantly associated with CA in patients with AS. Higher overall mortality in the 178 patients with AS + CA in comparison to 1,220 patients with AS alone was observed [odds ratio (OR) 2.25, p = 0.004]. Meta-regression analysis showed that younger age and diabetes were associated with overall mortality in patients with CS with CA (Z-value −3.0, p = 0.003 and Z-value 2.5, p = 0.013, respectively). Finally, patients who underwent surgical aortic valve replacement (SAVR) or transcatheter aortic valve implantation (TAVI) had a similar overall mortality risk, but lower than medication-treated only patients. Conclusion Results from our meta-analysis suggest that several specific clinical, electrocardiographic, and echocardiographic features can be considered “red flags” of CA in patients with AS. CA negatively affects the outcome of patients with AS. Patients with concomitant CA and AS benefit from SAVR or TAVI.